Południkowa zmienność warunków radiacyjnych w obrębie gniazd na terenie Polski – wyniki modelowania - Bolibok, Leszek; Brach, Michał; Drozdowski, Stanisław; Szeligowski, Henryk (Leśne Prace Badawcze, 2016)
The aim of the study was to characterize latitudinal changes in the radiative microclimate of small forest openings (artificial gaps) under Polish conditions. The global, direct and diffuse radiation on the forest floor in gaps was modelled using the Solar Radiation tool in ArcGiS 10.2 Esri. The gaps were modelled as holes of elliptical shape (60m x 40m diameters) in flat terrain and with a depth of 20 to 30 meters to mimic the height of a surrounding tree stand. The range of global radiation diversity on an open and flat surface predicted by our model was comparable with findings of empirical studies. Theoretically, the investigated gaps in the northern-most part of Poland receive only 82% of global solar radiation, 74% direct and 90% of diffuse radiation compared to gaps in the most southern part of the country. The comparison with empirical data indicates that local values of the transmittance parameter of the atmosphere may have a large influence on the actual values of solar radiation and may partially mask the latitudinal impact. Nevertheless, the model constitutes a valuable tool for characterizing solar radiation diversity in a gap and supports silvicultural decision-making.